Detection of some major elements and protein in Fusarium wilt disease infected tomato(Lycopersicon esculentum) treated with Arbuscular mycorrhizal fungi (Journal of the College of Basic Education, 2022)
The present study was Conducted to evaluate the effect of amixture of three species of arbuscular mycorrhizal fungi ( Glomus etunicatum , G. leptotichum and Rhizophagus intraradices ) in Influence on the percentage of the components of NPK and protein of tomato leaves and roots infected with Fusarium oxysporum f.sp. Lycopersici wich cause Fusarial wilt disease , planted for 8 weeks in the presence of the organic matter ( peatmose) , using pot cultures in aplastic green house , Results indicated significant increase in the percentage of the elements of NK and protein of tomato leaves and roots In the control treatment (C), While the percentage of the element P was after infection with the pathogen 4 weaks after mycorrhizal colonization in all treatments ( single , dual and trial interactions) . on the other hand mycorrhizal colonization of the leaves and roots in the presence of organic matter and pathogen after 4 weaks of pathogen infection resulted in significant increase in the percentage of the elements of NK and protein of leaves and roots in all treatment ( single , dual and trial interaction ) . The treatment ( M+ × O+ x C) Showed the highest Percentage followed by the trial ( M+ × 4W+ x O+) , The P element was the highest in the treatment of trial interaction ( M+ × 4W+ x O+) followed by the dual ( M+ x 4W+ ), whereas the lowest decline in the ratio of the elements and protein for all treatments was shown at the time of plantation ( OW+ ) in the presence of the pathogen . Overall, the study showed an increase in the percentage of the elements of NPK and protein in the leaves than the roots.